Answers

2014-04-01T13:29:13+05:30
 x^{2} - y^{2} =27...............1 \\ x+y=3...............2 \\ from eq. 2 \\ x=3-y
putting the value of x in 1
 (3-y)^{2} + y^{2} =27 \\ 9+ y^{2} -6y- y^{2} =27 \\ -6y=18 \\ y=-3
putting the value of y in 2
x-3=3 \\ x=6 ans..
0
2014-04-01T14:22:33+05:30
We know that x2 - y2= (x+y)(x-y)
therefore our equation becomes (x+y)(x-y) = 27

we know that x+y = 3............................................................(1)
therefore    3(x-y)=27
x - y= 9................................................................................(2)

from (1) and (2).....we get  x=  6
and                                 y= (-3)

1 5 1